Survey of Facilities for Runaway and Homeless Youth, 1983-1988 - Swicord, Donald ([Verlag nicht ermittelbar], 1989)
This data collection is a compilation of demographic and service information collected on youths in residential and nonresidential shelters for runaways and homeless youths. The data provide descriptions of the youths using the shelters and offer data on age, sex, race, education, family setting, shelter services provided, and aftercare services received.